ChemInform Abstract: A Palladium‐Catalyzed Three‐Component‐Coupling Strategy for the Differential Vicinal Diarylation of Terminal 1, 3‐Dienes. Issue 8 (February 2015) - Stokes, Benjamin J.; Liao, Longyan; de Andrade, Aline Mendes; Wang, Qiaofeng; Sigman, Matthew S.
Abstract An interesting vicinal diarylation of terminal 1, 3‐dienes is developed using a reagent mixture of aryldiazonium tetrafluoroborates and arylboronic acids.